Proceedings of IEEE Sensors, 2004.
DOI: 10.1109/icsens.2004.1426270
|View full text |Cite
|
Sign up to set email alerts
|

Nanocharacterization of a novel copper-membrane and functionalized insulator-semiconductor by atomic force microscopy

Abstract: We describe the characterization of a novel coppersensitive polymeric membrane and the electrochemical response of electrolyte-membrane-insulator-semiconductor structures. The membrane has shown a nernstian response towards Cu(II) ions in electrodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 6 publications
(8 reference statements)
0
10
0
Order By: Relevance
“…Schwake et al applied AFM to study the origin of asymmetry potentials observed with ion-selective polymer matrix membranes [22]. The tip of the atomic force microscope has been silanized to nanocharactarize the surface of a Cu(II) PVC-membrane electrode [23]. De Marco et al used AFM cantilever comprising a copper ion selective electrode tip to differentiate between a copper releasing and non-copper releasing substrates [24].…”
Section: Doi: 101002/elan201100521mentioning
confidence: 99%
See 1 more Smart Citation
“…Schwake et al applied AFM to study the origin of asymmetry potentials observed with ion-selective polymer matrix membranes [22]. The tip of the atomic force microscope has been silanized to nanocharactarize the surface of a Cu(II) PVC-membrane electrode [23]. De Marco et al used AFM cantilever comprising a copper ion selective electrode tip to differentiate between a copper releasing and non-copper releasing substrates [24].…”
Section: Doi: 101002/elan201100521mentioning
confidence: 99%
“…The main advantage of AFM compared to SEM is its ability to image the surface in situ as it experiences its inherent solution chemistry [23,24]. In addition, AFM can image a plastic membrane surface in its natural state without neither coating nor subjecting to a highly reduced pressure.…”
Section: Doi: 101002/elan201100521mentioning
confidence: 99%
“…4-Phenyl-4-sulfide-11-(1-oxodecyl)-1,7-dithia-11-aza-4-phosphacyclotetradecane (compound A), figure 1, has a thiomacrocycle that permits to bind copper ions, so acting as a copper ionophore [44,45]. A comparison of the mechanical properties of LB films of compound A extracted either from the water subphase or from the Cu(II) aqueous solution subphase offers the opportunity to study the influence of Cu(II) ions in the rheological properties of LBs of compound A.…”
Section: Introductionmentioning
confidence: 99%
“…The ligand 4-phenyl-4-sulfide-11-(1-oxodecyl)-1,7-dithia-11-aza-4-phosphacyclotetradecane (IV) was synthesized according to previously published method [25]. This macrocycle (IV) was prepared by the sulfuration of the phosphamacrocycle III, obtained previously by cyclation of I and II using high dilution techniques (20 ml/h addition rate of I and II 18.1 mmol THF solutions over 500 ml THF) (Fig.…”
Section: Synthesis Of the Ligandmentioning
confidence: 99%
“…We have recently developed copper(II)-ion selective electrode using this novel ligand [25]. In that work, the conductive solid internal was graphite/epoxy [26].…”
Section: Introductionmentioning
confidence: 99%